QR Code-Based Digital Media for Scientific Literacy Skills Enhancement of Elementary School Students - Kartika Sari, Pratiwi; Nabilla Qonita, Dzakiyah (JTP - Jurnal Teknologi Pendidikan, 2024)
QR Code-based learning encourages teachers to be more creative in designing lessons and students to become more active in the learning process. The problems that are present are the low literacy skills of students in the field of science education, the lack of ability in the field of digital-based technology for science literacy learning, describing alternative solutions to improve science literacy in elementary school students. The development of learning materials in the form of QR Code-based E-Modules aims to enhance higher-order thinking skills in thematic learning. This research aims to develop, validate, and assess effectiveness development of QR Code-Based digital media to enhance scientific literacy skills in the teaching of natural sciences. The research design follows the Research and Development (R&D) method, specifically the Richey and Klein method, consisting of three stages: Planning, Production, and Evaluation. Validation results from media experts show a percentage of 91.57%, language experts 84.38%, and content experts 96.13%. Thus, the developed product is considered highly feasible and ready for testing. The next stage involves one-to-one testing, small group testing, and field testing. One-toone testing scores were 90.28%, small group testing was 93.33%, and field testing was 85.74%. To verify the accuracy of the data, a paired sample t-test using SPSS is conducted, resulting in significance = 0.000 < 0.05. Therefore, it can be concluded that implementing QR Code-based digital media in science education has a significant positive effect, making it highly feasible and effective for use in fourth-grade science classrooms. Thus with this research students’ abilities in implementing scientific literacy in everyday life can be improved to achieve better learning outcomes.